Sistema mobile web para busca georreferenciada de imóveis - Mendes, Gláucia Maria Pastro (2011)
This work presents a study on mobile web development tools, with emphasis on the jQuery framework API and Google Maps Mobile. Here are given the tools and technologies and their application for the construction of a system of real estate search by user Geolocation, entitled Cadê Meu Apê. This system has as main characteristic the use of an interface that fits well for viewing on desktops and mobile devices.